Morphology and histology of the uropygial gland in Antarctic birds: relationship with their contact with the aquatic environment? - Chiale, Maria Cecilia (2014)
The uropygial gland is morphologically different in diverse bird species. This gland was macroscopically and microscopically examined in penguins, storm petrels and skuas. In all the studied species, the gland showed a connective tissue capsule and one papilla. A negative relationship was observed between the relative glandular mass and the body mass, being highest in petrels (small glands) and lowest in penguins (large glands). Birds that spend much time in water (penguins) have gland characteristics related to a continuous, but not stored, secretion, such as straight adenomers, the presence of abundant elastic fibres in the connective tissue and the absence of a primary storage chamber. Instead, birds that have less contact with water (storm petrels) have a gland with much more tortuous adenomers and a small primary storage chamber. The secretory cells showed a positive PAS reaction in all the glandular zones. Therefore, no differences could be seen between the sebaceous and glucogenic zones, as proposed in other birds. These results allow the conclusion that, in aquatic birds, there is no connection between the relative mass of the uropygial gland and the time in contact with water, though the differences found in the histological structure could be related to a different contact with the aquatic environment.